Social Inclusion; Practical Strategies to Promote Equality of Socio-Economics In Islamic Economic Framework - Dwi Sulastyawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Abstract;Indonesian economic condition for the last decade increases its rate of economic growth. Unfortunately, it also raises the rate of inequality of income distribution of people. In this case, needed any integrated strategy to slow down inequality to attain equality of socio-economics of community. Social inclusion in Islamic economic perspective is one of the key policy ingredients to attain stable and just economic development of society. Social inclusion is focusing on creating conditions for equal opportunities and equal access for all in all aspect of life. Social inclusion means full and active participation of every member of society in all aspect of life including; civic, social, economic, and political activities. This paper will examine the concept of social inclusion focused on economical aspect. In this context, social inclusion can be understood as the process by which society combatting poverty. Combatting poverty means to remove the main factor of social exclusion. Participation and inclusiveness should structure the new approach to combating poverty. This requires paradigm shift from exclusion to inclusion.  More than that it should be; ethical norm, moral imperative, allowable principal and societal purpose, and hand in hand with economic system of Islam. One of the strategies to promote equality of socio-economic is consideration, the concern on needs of individuals and group. Integrated objective from this subject is to reduce poverty, employment opportunity, and sustainable development. This is in line with the objective of Islamic economic system to attain equality of income distribution of all of society. Methodology of paper on this subject is developmental research. In developmental research, the theory of social inclusion is reproduced, rectified, and perfected in line with Islamic economic framework. There are many researches regarding social inclusion, this paper specifically discusses social inclusion in promoting equality of socio-economic in Islamic economic perspective.Keywords: Social inclusion, socio-economics, Islamic economic. Abstrak:Kondisi perekonomian Indonesia selama satu dekade terakhir meningkatkan laju pertumbuhan ekonominya. Sayangnya, hal tersebut juga meningkatkan tingkat ketimpangan distribusi pendapatan masyarakat. Dalam hal ini, diperlukan strategi terpadu untuk memperlambat ketimpangan untuk mencapai kesetaraan sosial ekonomi masyarakat. Inklusi sosial dalam perspektif ekonomi Islam merupakan salah satu bahan kebijakan utama untuk mencapai pembangunan ekonomi masyarakat yang stabil dan berkeadilan. Inklusi sosial berfokus pada penciptaan kondisi untuk kesempatan yang sama dan akses yang sama untuk semua dalam semua aspek kehidupan. Inklusi sosial berarti partisipasi penuh dan aktif dari setiap anggota masyarakat dalam semua aspek kehidupan termasuk; kegiatan sipil, sosial, ekonomi, dan politik. Makalah ini akan mengkaji konsep inklusi sosial yang difokuskan pada aspek ekonomi. Dalam konteks ini, inklusi sosial dapat dipahami sebagai proses yang digunakan masyarakat untuk memerangi kemiskinan. Memerangi kemiskinan berarti menghilangkan faktor utama pengucilan sosial. Partisipasi dan inklusivitas harus menyusun pendekatan baru untuk memerangi kemiskinan. Hal ini membutuhkan pergeseran paradigma dari eksklusi ke inklusi. Lebih dari itu seharusnya; norma etika, keharusan moral, prinsip dan tujuan masyarakat yang diperbolehkan, dan sejalan dengan sistem ekonomi Islam. Salah satu strategi untuk mendorong pemerataan sosial ekonomi adalah dengan memperhatikan kebutuhan individu dan kelompok. Tujuan terpadu dari mata pelajaran ini adalah untuk mengurangi kemiskinan, kesempatan kerja, dan pembangunan berkelanjutan. Hal ini sejalan dengan tujuan sistem ekonomi Islam untuk mencapai pemerataan distribusi pendapatan seluruh masyarakat. Metodologi penulisan pada subjek ini adalah penelitian pengembangan. Dalam penelitian pembangunan, teori inklusi sosial direproduksi, diperbaiki, dan disempurnakan sejalan dengan kerangka ekonomi Islam. Banyak penelitian mengenai inklusi sosial, tulisan ini secara khusus membahas tentang inklusi sosial dalam mempromosikan kesetaraan sosial ekonomi dalam perspektif ekonomi Islam.Kata kunci: Inklusi sosial, sosial ekonomi, ekonomi Islam.